2022
DOI: 10.1371/journal.pgen.1010160
|View full text |Cite
|
Sign up to set email alerts
|

Patagonian sheepdog: Genomic analyses trace the footprints of extinct UK herding dogs to South America

Abstract: Most modern dog breeds were developed within the last two hundred years, following strong and recent human selection based predominantly on aesthetics, with few modern breeds constructed solely to maximize their work potential. In many cases, these working breeds represent the last remnants of now lost populations. The Patagonian sheepdog (PGOD), a rare herding breed, is a remarkable example of such a population. Maintained as an isolated population for over 130 years, the PGOD offers a unique opportunity to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Chiefly, genetic polymorphisms associated with breed differences in cognitive processes, including inhibitory control, communication, memory, and physical reasoning are starting to be identified and are further reflected in neuroanatomical variation across breeds (Gnanadesikan et al, 2020;Hecht et al, 2019). Tracing canine lineages via modern breed genetics can also, in some instances, be a useful proxy for investigating historic human population movements and associated cultural variation (Barrios et al, 2022;Bergström et al, 2020;Perri et al, 2021). However, fully leveraging modern dog breed diversity as one of the most significant "real-time" multipurpose evolutionary genetics experiments relies on overcoming the limitations of small sample sizes; coordinated data sharing efforts such as ManyDogs can help to achieve this goal.…”
Section: Evolutionary Origins Of Cognition and Behaviormentioning
confidence: 99%
“…Chiefly, genetic polymorphisms associated with breed differences in cognitive processes, including inhibitory control, communication, memory, and physical reasoning are starting to be identified and are further reflected in neuroanatomical variation across breeds (Gnanadesikan et al, 2020;Hecht et al, 2019). Tracing canine lineages via modern breed genetics can also, in some instances, be a useful proxy for investigating historic human population movements and associated cultural variation (Barrios et al, 2022;Bergström et al, 2020;Perri et al, 2021). However, fully leveraging modern dog breed diversity as one of the most significant "real-time" multipurpose evolutionary genetics experiments relies on overcoming the limitations of small sample sizes; coordinated data sharing efforts such as ManyDogs can help to achieve this goal.…”
Section: Evolutionary Origins Of Cognition and Behaviormentioning
confidence: 99%
“…Chiefly, genetic polymorphisms associated with breed differences in cognitive processes, including inhibitory control, communication, memory, and physical reasoning are starting to be identified, and are further reflected in neuroanatomical variation across breeds (Hecht et al, 2019;Gnanadesikan et al, 2020). Tracing canine lineages via modern breed genetics can, in some instances, also be a useful proxy for investigating historic human population movements and associated cultural variation (Bergström et al, 2020;Perri et al, 2021;Barrios et al, 2022). However, fully leveraging modern dog breed diversity as one of the most significant "real-time" multi-purpose evolutionary genetics experiments relies on overcoming the limitations of small sample sizes; coordinated data sharing efforts such as ManyDogs can help to achieve this goal.…”
Section: Evolutionary Origins Of Cognition and Behaviormentioning
confidence: 99%
“…Many of the canine, solely breed-assignment studies were performed by microsatellite markers in spite of the fact that SNPs have found their way to describe structure, admixture, and possible origin of the studied breeds [ 15 , 16 ]. More recent investigations, conducted mainly in cattle as another domestic species, demonstrated that the effectiveness of breed assignment experiments can be enhanced further by selecting only the most informative, so-called breed-informative, SNP-set [ 17 ].…”
Section: Introductionmentioning
confidence: 99%